Oxidation of Organic Substrates with RuIV=O Complexes Formed by Proton-Coupled Electron Transfer - Ishizuka, Tomoya; Ohzu, Shingo; Kojima, Takahiko (Synlett, 2014)
We describe our recent progress in mechanistic investigations on substrate oxidation reactions with RuIV=O complexes having pyridylamine ligands. The RuIV=O complexes are synthesized from the corresponding RuII–OH2 complexes either through a proton-coupled electron-transfer procedure using a cerium(IV) complex as an oxidant or by bulk electrolysis. We have verified the presence of an adduct-formation equilibrium between the RuIV=O complex and a substrate in water, which strongly affects the reaction mechanism of the substrate oxidation. We have also shown that the reaction rates of the substrate oxidation in water are independent of the spin states of the RuIV centers and of the bond-dissociation enthalpy of the C–H bond of the substrate. Additionally, we have applied the RuII–OH2 complexes as catalysts for photocatalytic substrate oxidations and have observed very efficient catalytic activity.1 Introduction2 Formation, Characterization, and Reactivity of RuIV=O Complexes by Using a Peroxide as an Oxidant3 Formation and Characterization of RuIV=O Complexes by a Proton-Coupled Electron-Transfer Procedure4 Catalytic Oxidation of Organic Substrates by Proton-Coupled Electron-Transfer Oxidation5 Kinetic Studies on Substrate Oxidations with RuIV=O Complexes6 Photocatalytic Oxidation of Organic Substrates7 Concluding Remarks
Keywords: ruthenium; metal-oxo complex; substrate oxidation; proton-coupled electron transfer; pre-equilibrium process; photocatalytic oxidation